Unveiling Mysticism and Community Engagement in Indonesian Ritual Performances - Pramestiwi, Davina Ardaneza; Sinduwiatmo, Kukuh (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Culture is a dynamic method that evolves within communities, shaping their identities and practices. Specific Background: This study focuses on the ritual communication involved in the traditional art of Jaranan Branasti Putro, originating from Ringinsari village in Kediri Regency, Indonesia. Jaranan is a performance art infused with mystical elements, often featured in celebratory events. Knowledge Gap: While the significance of ritual communication in traditional arts is recognized, comprehensive analysis of its role in Jaranan performances remains underexplored. Aims: This research aims to investigate the various stages of ritual communication in Jaranan Branasti Putro and their impact on audience appreciation. Results: Utilizing a descriptive qualitative method, the study collected data through purposive sampling interviews, documentation, and observations, revealing that ritual communication is not only central to the performance but also contributes to the overall entertainment value of Jaranan. Novelty: This research highlights the dual nature of Jaranan art as both a mystical and entertaining practice, emphasizing the importance of community involvement in sustaining this cultural expression. Implications: The findings underscore the need for continued support and engagement within the community to preserve the Jaranan Branasti Putro tradition, ensuring its relevance and accessibility for future generations. Highlights: Jaranan Branasti Putro blends mysticism with entertainment in performances. Ritual communication stages enhance audience engagement and appreciation. Community involvement sustains cultural traditions and practices. Keywords: Jaranan, ritual communication, traditional art, community culture, qualitative research